1996
DOI: 10.1007/s004649900147
|View full text |Cite
|
Sign up to set email alerts
|

The impact of laparoscopic cholecystectomy on the treatment of symptomatic cholelithiasis

Abstract: The indication for surgery in cholelithiasis has not changed since the introduction of LC. In patients with symptomatic gallstones, early elective surgery is recommended and may be more cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Postoperative hospital stay in the present series was in agreement with other reports [5–8, 14, 19, 20], although in some centres, MC is now performed as day‐case or ambulatory surgery [21]. The results of MC in acute cholecystitis in this study compare favourably with those reported for LC [9, 16, 17], but the costs are lower [6, 21]. Avoiding the need for special instruments improves the cost‐effectiveness of MC.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Postoperative hospital stay in the present series was in agreement with other reports [5–8, 14, 19, 20], although in some centres, MC is now performed as day‐case or ambulatory surgery [21]. The results of MC in acute cholecystitis in this study compare favourably with those reported for LC [9, 16, 17], but the costs are lower [6, 21]. Avoiding the need for special instruments improves the cost‐effectiveness of MC.…”
Section: Discussionsupporting
confidence: 89%
“…In the emergency setting of acute cholecystitis, LC is gaining popularity rapidly and good results have been reported [16, 17]. However, the conversion rate to open cholecystectomy is still high, varying between 16% and 35% [16, 17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This trend has already eliminated the anticipated cost savings of laparoscopic cholecystectomy for the payors [4]. By contrast, Ho et al [7] in a study of cholecystectomy from 1988 to 1994 reported that their cholecystectomy rate had stabilized at a level only 11% higher than in the years preceding the introduction of laparoscopic cholecystectomy. This finding could be explained by the fact that theirs is a tertiary referral center and may not reflect what is happening in the country as a whole.…”
Section: Discussionmentioning
confidence: 92%
“…Most of these reports describe permanently higher surgical rates, unlike the 20.8% increase in Sweden in 1992, which was followed by a gradual reduction during the next 3 years [5]. Even though reports on unaltered cholecystectomy rates have been published from North Carolina [18] and California [9], the indications for cholecystectomy may have changed in the United States and Australia, perhaps due to an increased acceptance of a procedure offering less postoperative pain and a shorter convalescence period. The increased rate of cholecystectomy is probably not appropriate because some patients might be better off with conservative treatment.…”
Section: Scandinavia Versus Other Countriesmentioning
confidence: 94%